Non-OO blood type influences the risk of recurrent venous thromboembolism - Gándara, Esteban; Kovacs, Michael J.; Kahn, Susan R.; Wells, Philip S.; Anderson, David A.; Chagnon, Isabelle; Gal, Grégoire Le; Solymoss, Susan; Crowther, Mark; Carrier, Marc; Langlois, Nicole; Kovacs, Judy; Ma, Julian Little; Carson, Nancy; Ramsay, Tim; Rodger, Marc A. (Thrombosis and Haemostasis, 2013)
The role of ABO blood type as a risk factor for recurrent venous thromboembolism (VTE) in patients with a first unprovoked VTE who complete oral anticoagulation therapy is unknown. The aim of this study was to determine if non-OO blood type is a risk factor for recurrent VTE in patients with a first unprovoked VTE who completed 5–7 months of anticoagulant therapy. In an ongoing cohort study of patients with unprovoked VTE who discontinued oral anticoagulation after 5–7 months of therapy, six single nucleotide polymorphisms sites were tested to determine ABO blood type using banked DNA. The main outcome was objectively proven recurrent VTE. Mean follow-up for the cohort was 4.19 years (SD 2.16). During 1,553 patient-years of follow-up, 101 events occurred in 380 non-OO patients (6.5 events per 100 patient years; 95% CI 5.3–7.7) compared to 14 events during 560 patient years of follow-up in 129 OO patients (2.5 per 100 patient years; 95% CI 1.2–3.7), the adjusted hazard ratio was 1.98 (1.2–3.8). In conclusion, non-OO blood type is associated with a statistically significant and clinically relevant increased risk of recurrent VTE following discontinuation of anticoagulant therapy for a first episode of unprovoked VTE.
Keywords: Veins; thrombosis; blood cells